A new species of tree-hole dwelling freshwater crab of the genus Arachnothelphusa Ng, 1991 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from northern Sarawak, Malaysia, Borneo - Jongkar, Grinang; Pui, Yong Min; Ng, Peter K. L. (National University of Singapore, 2015)
A new species of tree-hole gecarcinucid freshwater crab, Arachnothelphusa merarapensis, is described from a primary dipterocarp forest near Merarap Hot Spring Resort in Lawas, northern Sarawak, Malaysia. This brings the number of species in the genus Arachnothelphusa found in Borneo to five, and it is likely that more species will be discovered from this island. The new species has preference for living in water-filled tree-holes, which is the first record of a tree-hole crab for Southeast Asia. The habitat characteristics and distribution of this new species are also discussed.